2023
DOI: 10.1038/s41612-023-00429-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct decadal modulation of Atlantic-Niño influence on ENSO

Abstract: It is known that winter Atlantic-Niño events can induce the El Niño–Southern oscillation (ENSO) in the following winter with a lag of 1-year during one period. On the other hand, summer Atlantic-Niño events can lead to the ENSO in the subsequent winter with a half-year lag during another period. In this study, we investigate the distinct interdecadal modulation of the effect of the Atlantic-Niños on ENSO by analyzing observational reanalysis datasets. During the mid-twentieth century, the winter Atlantic-Niño … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…We find that during 1975–1985 the tropical South Atlantic and eastern Pacific is warmer, and the ITCZ is shifted south toward the equator. An equatorward shifted ITCZ can facilitate a stronger atmospheric response of the equatorial Pacific (Park et al., 2023). The atmospheric response to an Atlantic Niño given this background state reflects a more westward location of surface convergence and upper‐level divergence in the Atlantic with respect to the response during 1950–1960.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that during 1975–1985 the tropical South Atlantic and eastern Pacific is warmer, and the ITCZ is shifted south toward the equator. An equatorward shifted ITCZ can facilitate a stronger atmospheric response of the equatorial Pacific (Park et al., 2023). The atmospheric response to an Atlantic Niño given this background state reflects a more westward location of surface convergence and upper‐level divergence in the Atlantic with respect to the response during 1950–1960.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Atlantic Niño variability may also be weakening (Crespo et al., 2022; Prigent et al., 2020; Yang et al., 2022), which could reduce the atmospheric response to Atlantic Niños. On the other hand, the boreal winter peak of the Atlantic Niño could become more important for ENSO predictions as the summer peak weakens (Hounsou‐Gbo et al., 2020; Park et al., 2023). Lastly, the results here also suggest that the ANN‐ENSO teleconnections can be hampered in models by systematic biases in the global SST pattern and the ITCZ position.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (e.g., Park et al, 2023) found that the influence of "summer" Atlantic Niño on ENSO has strengthened since the late 1970s (Figure S7 in Supporting Information S1). However, our focus is on the "winter" Atlantic Niño, and its relationship with subsequent ENSO has remained remarkably constant in recent years (dashed line in Figure S7 in Supporting Information S1; purple line in Figure S8 in Supporting Information S1).…”
Section: Inter-decadal Stabilitymentioning
confidence: 87%
“…As El Niño decays during the summer, the Indo-western Pacific Ocean capacitor effect sustains the warming of SST in the tropical North Indian Ocean [21] , thus maintaining the impact of ENSO on TP summer precipitation. With regard to the North Atlantic SST, El Niño can trigger a tripolar SST pattern in the North Atlantic, a phenomenon that often persists into the summer [24] . This tripolar pattern exerts a remote influence on the summer precipitation in the Tibetan Plateau through teleconnections [25] .…”
Section: Introductionmentioning
confidence: 99%